2012
DOI: 10.1590/s1984-70332012000300001
|View full text |Cite
|
Sign up to set email alerts
|

Tagging microsatellite marker to a blast resistance gene in the irrigated rice cultivar Cica-8

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Pinheiro et al . [ 13 ] developed the cultivar Cica-8 by crossing the susceptible cultivar Metica-1 to the resistant cultivar Cica-8, and they found that one microsatellite marker, RM7102, was closely linked to the resistant allele. Yang et al [ 132 ], while working on identifying and mapping the Pi41 gene, utilized resistant cultivar 93-11 and susceptible cultivar Nipponbare, as well as an F 2 population derived from a cross of these two cultivars.…”
Section: Microsatellites For Tracking Blast Resistance In Ricementioning
confidence: 99%
See 1 more Smart Citation
“…Pinheiro et al . [ 13 ] developed the cultivar Cica-8 by crossing the susceptible cultivar Metica-1 to the resistant cultivar Cica-8, and they found that one microsatellite marker, RM7102, was closely linked to the resistant allele. Yang et al [ 132 ], while working on identifying and mapping the Pi41 gene, utilized resistant cultivar 93-11 and susceptible cultivar Nipponbare, as well as an F 2 population derived from a cross of these two cultivars.…”
Section: Microsatellites For Tracking Blast Resistance In Ricementioning
confidence: 99%
“…Identifying resistance genes using molecular markers is the basic prerequisite for performing MAS in resistance breeding programs [ 13 ]. PCR-based microsatellite markers have attracted a great deal of attention due to several key advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Significance of molecular markers in this study is that there is no other clear-cut validation procedure for quantifying disease resistance. ISSR and SSR primers are proved to be efficacious in tagging resistant genes by many workers [47][48][49]. The ISSR marker UBC857 and SSR marker mTcCIR42 was figured to be linked with VSD resistance by Chandrakant, (2014) [25] and further validated by Tulshiram, (2016) [26].…”
Section: Resultsmentioning
confidence: 99%
“…This can be done with DNA marker-assisted selection. In many crops, DNA markers have been successfully used, of which E Matsuo et al microsatellites and SNPs (Single Nucleotide Polymorphism) are the most commonly used for the selection and mapping of genomic regions associated with genes and QTLs, as in soybean (Fuganti et al 2004, Morceli et al 2008, Dias et al 2009), rice (Pinheiro et al 2012) and maize (Teixeira et al 2013). Certainly, microsatellite markers have been used due to their high polymorphism, codominance, reproducibility and good distribution throughout the genome Grattapaglia 1998, Song et al 2004).…”
Section: Introductionmentioning
confidence: 99%